Attitudes of women from five European countries regarding tobacco control policies. Issue 2 (March 2013) - Dresler, Carolyn; Wei, Mei; Heck, Julia E.; Allwright, Shane; Haglund, Margaretha; Sanchez, Sara; Kralikova, Eva; Stücker, Isabelle; Tamang, Elizabeth; Gritz, Ellen R.; Hashibe, Mia
Aims : Tobacco-related cancers and, in particular, lung cancer still represents a substantial public health epidemic across Europe as a result of high rates of smoking prevalence. Countries in Europe have proposed and implemented tobacco control policies to reduce smoking prevalence, with some countries being more progressive than others. The aim of this study was to examine factors that influenced women's attitudes across five European countries relative to comprehensive smokefree laws in their countries. Methods : A cross-sectional landline telephone survey on attitudes towards tobacco control laws was conducted in five European countries: France, Ireland, Italy, the Czech Republic, and Sweden. Attitudinal scores were determined for each respondent relative to questions about smokefree laws. Logistic regression models were used to obtain odds ratios with 95% confidence intervals. Results : A total of 5000 women were interviewed (1000 women from each country). The majority of women, regardless of smoking history, objected to smoking in public buses, enclosed shopping centers, hospitals, and other indoor work places. More women who had quit smoking believed that new tobacco control laws would prompt cessation – as compared with women who still smoked. Conclusions : In general, there is very high support for national smokefree laws that cover bars, restaurants, and public transport systems. As such laws are implemented, attitudes do change, as demonstrated by the differences between countries such as Ireland and the Czech Republic. Implementing comprehensive smokefree laws will gain high approval and will be associated with prompting people to quit.